The Effectiveness of Using Problem-based Learning Methods in Improving Students' Reading Comprehension - Akuba, Tiansi; Pido, Nur Wahidah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2024)
Reading comprehension is the foundation of reading since it seeks to grasp the meaning of the reading material. One approach to improving pupils' reading comprehension is to employ the Problem Based Learning (PBL) learning method. This study sought to determine the efficiency of the Problem Based Learning method in enhancing students' reading comprehension. This study employs a comprehensive literature review approach. Research activities or analysis are carried out by gathering article data from national journals that may be accessible through Google Scholar over the last five years (2020-2024) relating to the issue under consideration. The study found that using the Problem Based Learning (PBL) learning style can help pupils enhance their reading comprehension.